Achieving the triple dividend in Portugal: a dynamic general-equilibrium evaluation of a carbon tax indexed to emissions trading. Issue 2 (3rd April 2019) - Pereira, Alfredo Marvao; Pereira, Rui Marvao
Abstract : Using a dynamic general equilibrium model, we simulate the environmental, economic, and budgetary effects in Portugal of a new carbon tax indexed to the carbon price in the European Union's Emissions Trading System market. Through careful recycling of the carbon tax revenues to finance lower personal income taxes, lower Social Security contributions, and higher investment tax credits – in particular when changes are directed at promoting energy efficiency – we show that it is possible to design a carbon tax reform that boosts economic growth and strengthens fiscal consolidation. These results served as the basis for a new carbon tax eventually approved by the Portuguese Parliament.